1997
DOI: 10.1097/00005768-199712000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal, immunological, and hematological responses to intensified training in elite swimmers

Abstract: The purpose of this study was to compare the responses of selected hormonal, immunological, and hematological variables in athletes showing symptoms of overreaching with these variables in well-trained athletes during intensified training. Training volume was progressively increased over 4 wk in 24 elite swimmers (8 male, 16 female); symptoms of overreaching were identified in eight swimmers based on decrements in swim performance, persistent high ratings of fatigue, and comments in log books indicating poor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
100
0
9

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 36 publications
13
100
0
9
Order By: Relevance
“…There were also no relationships found between T, C or T:C and CRP, CK or cf-DNA. These findings reiterate the results of previous research that found no consistent changes in T, C and T:C with changing training loads 31,32 and suggests that practitioners should use care when interpreting T:C.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There were also no relationships found between T, C or T:C and CRP, CK or cf-DNA. These findings reiterate the results of previous research that found no consistent changes in T, C and T:C with changing training loads 31,32 and suggests that practitioners should use care when interpreting T:C.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, testosterone, cortisol and T:C ratio in endurance athletes have not shown to respond consistently to increased or decreased training load or when overreached and overtrained. [31][32][33][34][35] There are also inconsistencies in resistance trained individuals. 36 The purpose of this study was to investigate changes in cf-DNA and other commonly used biochemical markers throughout a collegiate soccer season in order to examine the utility of cf-DNA as a potential variable to be included in a LTAMP for NCAA Division I collegiate soccer.…”
Section: Introductionmentioning
confidence: 99%
“…2) Parâmetros imunológicos a) Leucócitos: Normalmente, a quantidade de leucó-citos permanece dentro dos valores de referência, mesmo durante períodos de treinamento físico intenso e em atletas em OT [27,34,58]. Contudo, Lehmann et al [51] observaram em corredores uma diminuição da quantidade de leucócitos abaixo dos valores de referência, em resposta a um período de quatro semanas em que o volume, e não a intensidade de treinamento, foi dobrado.…”
Section: Diagnóstico Do Overtrainingunclassified
“…Gorostiaga et al [28] sugerem que uma queda inferior a 45% da razão T/C nem sempre pode indicar OT. d) Catecolaminas: Mudanças na concentração plasmática e excreção urinária da noradrenalina têm sido associadas com o OT [58]. Aumento e diminuição da concentração plasmática em repouso e após exercício de alta intensidade, respectivamente, foram registrados em corredores de meio fundo após perío-dos de treinamento intenso [46,49,51,58].…”
Section: Diagnóstico Do Overtrainingunclassified
See 1 more Smart Citation